Respuesta :

Algebra Calculator | Latest | Discuss | About | Help | Translation

20,897,614 solved | 1,346 online

Skip Ad
 5x2-23x=-26 Two solutions were found :  x = 2  x = 13/5 = 2.600

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                     5*x^2-23*x-(-26)=0 

Step by step solution :Skip Ad
Step  1  :Equation at the end of step  1  : (5x2 - 23x) - -26 = 0 Step  2  :Trying to factor by splitting the middle term

 2.1     Factoring  5x2-23x+26 

The first term is,  5x2  its coefficient is  5 .
The middle term is,  -23x  its coefficient is  -23 .
The last term, "the constant", is  +26 

Step-1 : Multiply the coefficient of the first term by the constant   5 • 26 = 130 

Step-2 : Find two factors of  130  whose sum equals the coefficient of the middle term, which is   -23 .

      -130    +    -1    =    -131
      -65    +    -2    =    -67
      -26    +    -5    =    -31
      -13    +    -10    =    -23    That's it